USING MAKE A MATCH CARDS ABOUT CELL TO IMPROVE STUDENTS’ LEARNING OUTCOME - Amelia Nur Safitri; Mohammad Budiyanto; Enny Susiyawati (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2020)
The research aimed to describe the use of make a match cards about cell to improve student learning outcome in term of knowledge. The feasiblity of the make a match card was reviewed in terms of the validity, practicalty, and effectiveness aspects. The research design used in this study was Research and Development (R&D). The validity aspect is obtained through the validation process by 2 lecturers and 1 science teacher using a validation sheet based on a Likert Scale. The results showed that the validity of the make a match card obtained modus value of 4 with a decent category. The practicalty and effectiveness aspects are carried out through a product trial process involving 29 junior high school students of SMP Negeri 50 Surabaya in grade 7th. The practicality of the make a match card in terms of the student activity sheet obtained an average percentage of 94,30% with a very practical category. Response questionnaire in terms of the observation sheet of student responses showed that 96,55% of students gave positive responses to use of the make a match card on sub cell material. The effectiveness of the make a match card was reviewed in terms of improving student learning outcomes obtained based on the results of the pretest and posttest that gained an average 0,61 0f N-Gain score with medium category. Based on the validity, particality, and effectiveness aspects, it can be concluded that the make a match card on sub cell material is appropriate to be utilized in learning.Keywords: Make a Match Cards, Cell, Learning Outcome